Lipid and energy contents in the bodies of queens of Atta sexdens rubropilosa Forel (Hymenoptera, Formicidae): pre-and post-nuptial flight - Fujihara, Ricardo Toshio [UNESP]; Camargo, Roberto da Silva [UNESP]; Forti, Luiz Carlos [UNESP] (Sociedade Brasileira de Entomologia, 2012)
O vôo nupcial permite que machos e fêmeas se encontrem e copulem. Para isso, tanto o macho quanto a fêmea precisam de energia para efetuar tal atividade. Antes de partir do ninho de origem, machos e fêmeas estão bem nutridos e prontos para o acasalamento. Mas pouco se conhece sobre o teor de lipídeos e conteúdo energético pré-vôo nupcial (fêmeas virgens) e pós-vôo nupcial (fêmeas acasaladas). Nossos resultados indicam que as fêmeas virgens apresentaram 16,82% de lipídeos em seu corpo, enquanto as rainhas (fêmeas acasaladas) que não escavaram 32,62%, e as que escavaram 32,88%. O conteúdo energético foi de 2942,63 J para as fêmeas virgens, 6110,01 J para rainhas sem escavação e 5677,51 J para aquelas que escavaram. Com base nos resultados obtidos, concluí-se que as rainhas de Atta sexdens rubropilosa dobram a sua massa corporal, e consequentemente, o teor de lipídeos e conteúdo energético, um mês antes da revoada. Esse recurso energético é fundamental para as atividades exigidas durante o vôo nupcial, escavação do ninho e a fundação da colônia.

The nuptial flight allows males and females to meet and copulate and both need energy to perform this activity. Before leaving the nest, males and females are well nourished and ready to mate. However, little is known about the lipid and energy contents in females before the nuptial flight (virgins) and after it (mated females). In this work we measured lipid concentrations in relation to body weight in these individuals. Our results showed that 16.82% of the bodies of young virgin females one month before mating flight are composed of lipids, contrasting with the 32.62% lipid content in mated females who had not excavated their nest yet, and 32.88% in those who had. The energy content measured for virgin females was 2942.63 J, contrasting with 6110.01 J for queens before excavating the nest and 5677.51 J after excavation. Based on our results, we conclude that the body mass, and therefore the lipid and energy contents in the bodies of Atta sexdens rubropilosa queens double during the last month before the nuptial flight. This energy resource is fundamental to the activities required during the nuptial flight, digging the nest and the founding of the colony.
Conteúdo de lipídeos e energético das rainhas de Atta sexdens rubropilosa Forel (Hymenoptera, Formicidae): pré e pós-vôo nupcial
Keywords: Conteúdo energético; fundação do ninho; teor de lipídeos; vôo nupcial; Energy content; lipid content; nest founding; nuptial flight